Detection of Mycotoxigenic Fungi on Food from Markets with the Polymerase Chain Reaction Method for Halal and Thoyiban Food - Mohammad Sukmanadi; Retno Sri Wahjuni; Kadek Rachmawati (Institute of Medico-legal Publications Pvt Ltd, 2021)
Secondary metabolites of filamentous mold are mycotoxins, which in some situations can develop on foodsderived from plants or from animals. Fusarium, Aspergillus, and Penicillium are the most common types ofmold that produce mycotoxins and also often contaminate human food and animal feed. Aflatoxins includingaflatoxin B1, B2, G1 and G2 are produced by A. flavus and A. parasiticus. M1 and M2 aflatoxins arefound in dairy products. In this study, we used PCR to detect and identify mycotoxigenic fungi material infoods from traditional markets and supermarkets in Surabaya, Indonesia. Samples of chicken meat from atraditional market and from a supermarket (10 pieces each) were placed in a conical tube and crushed in PBS.The crushed samples were centrifuged and the supernatants were cultured on potato dextrose agar (PDA)media and observed using a reverse microscope. DNA was isolated from cultured samples and subjectedto PCR with primers specific for genes encoding aflatoxins. Interestingly, we revealed that the PolymeraseChain Reaction (PCR) analysis showed A. flavus and A. ochraceus were present on chicken meat sold attraditional markets and supermarkets. In sum, enhanced precautions may be needed to ensure that foods soldin traditional markets and supermarkets are free from molds that have the potential to produce mycotoxins.Further studies are needed to detect and identify the prevalence of mycotoxins in the food supply.